Effect of the scanning path on the nanosecond pulse laser welded Al/Cu lapped joint. (July 2021) - Zhu, Baohua; Zhen, Liang; Xia, Hongbo; Su, Jianhui; Niu, Sicheng; Wu, Laijun; Tan, Caiwang; Chen, Bo
Abstract: In this research, Al/Cu lapped joints with a thickness of 0.2 mm were joined via nanosecond pulsed laser welding. The influence of laser scanning paths on the weld formation, microstructure and bonding strength was investigated. Sound weld formations were produced when the outer spiral laser scanning path was used. Porosities and cracks were easily formed in joints produced by concentric circle and straight laser scanning paths due to the interval duration between the neighboring welding processes. The interfacial morphology was a wave structure when the laser scanning paths were an outer spiral and concentric circle, and continuous interfacial intermetallic compound (IMC) was formed at the interface. θ–CuAl2 was generated in the vicinity of the Cu substrate, while α-Al + θ–CuAl2 was generated in the outer region and the weld seam. When a straight line laser scanning path was adopted, the wave structure disappeared. Discontinuous IMC and cracks were also produced at the interface. The tensile-shear load results indicated that the outer spiral laser scanning line was the most beneficial for the bonding strength of the joint and could reach up to 198 N. A satisfactory weld formation, the pinning effect due to the wave structure at the interface and continuous interfacial IMC all contributed to its highest bonding strength.